Pattern and Determinants of Overweight and Obesity Among Future Physicians - Basu, M; Das, P; Dhar, G; Datta, S; Chattopaddhyay, S; Bagchi, S; Pal, R (Nepal Journal of Epidemiology, 2014)
Background Overweight including obesity is a leading cause of present day morbidity and kills more people than underweight. Keeping this background in mind this study had been conducted to establish the pattern of overweight and obesity in the midst of undergraduate medical group and to find out the association of overweight (plump) and obesity with probable hazardous factors. Materials and Methods This descriptive observational study had been conducted among undergraduate medical group for the duration of May to June 2011. Simple random sampling was adopted to select the students under study. A pretested, predesigned self-administered questionnaire was utilized for data collection. Body Mass Index (BMI) was assessed through weight and height and acted as forecaster of heavy figure and or obesity. Overweight and or obesity were analyzed to see the association with certain socio-demographic variables, dietary habits, family history of overweight and or obesity, life style issues, computer use etc. After collection of data, these were analyzed using tabulation, proportion and Chi square through Epi-Info software. Results The study subjects were young adults. The general pattern of overweight (plump) and obesity was 18.0 percent and 4.0 percent respectively. Overweight and or obesity was found significantly high among male students, fast food and soft drinks takers, low takers of fruits and vegetables, alcohol consumers, students with lack of exercise and family history of obesity. Overweight and obesity were not found associated with type of diet (vegetarian or non-vegetarian) and smoking. Conclusion Presence of probable associated factors with regard to overweight (plump) and obesity exists amid medical undergraduate pupils. DOI: http://dx.doi.org/10.3126/nje.v4i1.10134 Nepal Journal of Epidemiology 2014;4 (1): 323-329